Education Assistance and Legal Consultation Related to Community Legal Protection in Digital Transactions - Kurniawan, Heru; Dungga, Weny Almorafid; Muhamad Khairun Kurniawan Kadir; Apripari; Elfikri, Nurul Fazri; Amrain, Fitran; Usman, Ramadhan; Daud, Akbar Hidayatullah (Edumedia Solution, 2026)
The development of digital technology has encouraged the increasing use of electronic transactions in various walks of life, including in rural areas. However, the rapid utilization of digital transactions has not been balanced with an adequate level of public understanding of the law, causing various legal risks such as online fraud, misuse of personal data, and legal uncertainty in electronic agreements. This community service activity aims to improve the legal literacy of the community through educational assistance and legal consultation related to legal protection in digital transactions. The method used is in the form of legal counseling and direct consultation held in Mekar Jaya village, Duhiadaa District, Pohuwato Regency, involving village officials and the general public. The results of the activities show that the public has been actively using digital transaction services, but still has a limited understanding of the legal rights and obligations as digital consumers. Through practical and contextual education, people are beginning to understand the importance of personal data protection, the validity of electronic agreements, and dispute resolution mechanisms in digital transactions. This legal assistance and consultation proved to be effective in increasing the legal awareness of the public and strengthening their position in facing the risks of digital transactions. This activity is expected to contribute to creating a secure, fair, and equitable digital transaction ecosystem, as well as being a model for sustainable legal service in the era of digital transformation.